Utilization of video-based learning media in Biology Lessons at MAN 1 Semarang - Irfan Aziz Adianto; Rohmat Nugroho; Naila Amalia; Riska Dami Ristanto (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
This research was carried out for aiming of producing learning media using the Quizizz platform; Knowing student responses and reactions regarding the use of video-based learning media and the Quizizz platform; and Knowing student learning outcomes from using video- and Quizizz-based learning media. The method used in research is Research and Development (R and D). The subjects in this study were students of class 10 MIPA 5 MAN 1 Semarang City totaling 36 students consisting of 11 boys and 21 girls. In this research, the implementation of R and D method research has 7 stages, namely potential and problems; data collection; product design; design validation; design revisions; product trials; analysis, and reporting. The results of this study indicate that: The application of video-based learning media and the Quizizz platform is classified as adequate; Video-based learning media and the Quizizz platform are well received; After the application of video-based learning media, the average value of student learning outcomes increased as enough criteria. AbstrakPenelitian ini dilaksanakan bertujuan untuk : Menghasilkan media pembelajaran dengan menggunakan platform Quizizz yang valid; Mengetahui respon dan tanggapan siswa mengenai penggunaan media pembelajaran berbasis Video dan platform Quizizz; Mengetahui hasil belajar siswa dari penggunaan media pembelajaran berbasis Video dan Quizizz. Metode yang digunakan pada penelitian adalah Research and Development (R and D). Subjek pada penelitian ini adalah siswa kelas 10 MIPA 5 MAN 1 Kota Semarang berjumlah 36 siswa terdiri dari 11 laki laki dan 21 perempuan. Pelaksanaan pada penelitian metode R and D memiliki 7 tahapan menurut Sugiyono dalam bukunya yang berjudul “Metode Penelitian Kuantitatif, Kualitatif dan R and D”), yaitu potensi dan masalah; pengumpulan data; desain produk; validasi desain; revisi desain; uji coba produk; analisis dan pelaporan. Hasil penelitian ini menunjukkan bahwa: Penerapan media pembelajaran berbasis video dan platform Quizizz tergolong kriteria cukup; Media pembelajaran berbasis video dan platform Quzizz diterima dan ditanggapi dengan baik oleh siswa; Setelah penerapan media pembelajaran berbasis video nilai rata-rata hasil belajar siswa meningkat dan tergolong kriteria cukup.Kata Kunci: Biologi; media pembelajaran; pembelajaran audio-visual